Determinants influencing revisit intention for ecotourism to Tasik Kenyir, Malaysia - Nordin, Nurul Afifah (2019)
The abundance of natural resources creates opportunities for Tasik Kenyir to become an attractive ecotourism site; the increase in the number of visitors implies the increase in demand for ecotourism activities and services in Tasik Kenyir. However, the increase in the number of visitors to Tasik Kenyir may not provide accurate information on the number of repeat visitors. Understanding the factors that influence the revisit intention to Tasik Kenyir is imperative as it helps the management of the ecotourism site to develop effective strategies in ecotourism marketing in at Tasik Kenyir. The main objective of this study is to identify the determinants influencing the revisit intention of visitors to Tasik Kenyir. In order to assess the factors influencing revisit intention of the visitors, the Theory of Planned Behavior (TPB) variables were examined together with additional variables, which included conservation awareness of the visitors, their visit characteristic and socio-demographic profiles. A structured questionnaire was designed as the instrument to gather data on the revisit intention to Tasik Kenyir. The questionnaires were distributed to the 319 sampled visitors in Tasik Kenyir using the non-probability sampling technique while the respondents were selected using the convenience sampling method. Descriptive analysis was used to measure the level of awareness variables included in the TPB and to identify the socio demographics and visit characteristics of visitors. While, a multiple linear regression analysis was used to analyse the determinants influencing the revisit intention of the visitors. Findings revealed that there were positively significant relationships between the level of conservation awareness, perceived behavioral control (PBC), and subjective norm and the revisit intention of visitors in Tasik Kenyir. The regression analysis showed that socio demographics and visit characteristics of visitors, types of occupation and types of accommodation used in Tasik Kenyir were the determinants that influenced the revisit intention of visitors to Tasik Kenyir. These findings can be used as a basis for further development of ecotourism facilities and services by the management at Tasik Kenyir. This study may also assist policy makers such as Terengganu Tengah Development Authority (KETENGAH), Tourism Terengganu and other agencies to formulate better conservational policies in order to encourage repeat visitations to Tasik Kenyir and to promote positive behaviors among the visitors toward the natural resource conservation efforts at Tasik Kenyir.